Small Group Discussion Strategies in Students' Reading Comprehension - Robiah, Dewi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study investigates the effectiveness of using small group discussion strategies in improving students' reading comprehension compared to whole-class teaching strategies. Conducted at SMPN 1 Banyakan, this research focuses on second-year students divided into experimental and control groups. The findings reveal a significant difference in students' reading comprehension between the two strategies. The small group discussion strategy promotes greater student participation, enhances motivation, and creates an interactive learning environment. In contrast, the whole-class strategy, though effective for general content delivery, limits personalized interaction and engagement. These results suggest that small group discussions are more effective for improving reading comprehension and addressing individual learning needs in classroom settings.